Epidemiological Characteristics of Foot and Ankle Injuries in 2 Professional Ballet Companies: A 3-Season Cohort Study of 588 Medical Attention Injuries and 255 Time-Loss Injuries. Issue 1 (26th December 2022) - Katakura, Mai; Kedgley, Angela E.; Shaw, Joseph W.; Mattiussi, Adam M.; Kelly, Shane; Clark, Richard; Allen, Nick; Calder, James D.F.
Background: The foot and ankle are often reported as the most common sites of injury in professional ballet dancers; however, epidemiological research focusing on foot and ankle injuries in isolation and investigating specific diagnoses is limited. Purpose: To investigate the incidence rate, severity, burden, and mechanisms of foot and ankle injuries that (1) required visiting a medical team (medical attention foot and ankle injuries; MA-FAIs) and (2) prevented a dancer from fully participating in all dance-related activities for at least 24 hours after the injury (time-loss foot and ankle injuries; TL-FAIs) in 2 professional ballet companies. Study Design: Descriptive epidemiological study. Methods: Foot and ankle injury data across 3 seasons (2016-2017 to 2018-2019) were extracted from the medical databases of 2 professional ballet companies. Injury-incidence rate (per dancer-season), severity, and burden were calculated and reported with reference to the mechanism of injury. Results: A total of 588 MA-FAIs and 255 TL-FAIs were observed across 455 dancer-seasons. The incidence rates of MA-FAIs and TL-FAIs were significantly higher in women (1.20 MA-FAIs and 0.55 TL-FAIs per dancer-season) than in men (0.83 MA-FAIs and 0.35 TL-FAIs per dancer-season) (MA-FAIs, P = .002; TL-FAIs, P = .008). The highest incidence rates for any specific injury pathology were ankle impingement syndrome and synovitis for MA-FAIs (women 0.27 and men 0.25 MA-FAIs per dancer-season) and ankle sprain for TL-FAIs (women 0.15 and men 0.08 TL-FAIs per dancer-season). Pointe work and jumping actions in women and jumping actions in men were the most common mechanisms of injury. The primary mechanism of injury of ankle sprains was jumping activities, but the primary mechanisms of ankle synovitis and impingement in women were related to dancing en pointe . Conclusion: The results of this study highlight the importance of further investigation of injury prevention strategies targeting pointe work and jumping actions in ballet dancers. Further research for injury prevention and rehabilitation strategies targeting posterior ankle impingement syndromes and ankle sprains are warranted.